Development of Mutualism Settlement Along the Railway Towards a Sustainable City - Gabriela Emilly Xian; Graciani Cahyadresta Dewanda; Rizky Olda Putri Salsabilla; Happy Ratna Sumartinah (Paragraphs Environmental Design, 2023)
The existence and development contribution of a village influences a sustainable city. Sidorukun Village is in the Gresik sub-district, Gresik district is dominated by settlements and industrial areas. In the middle of the village there is Indro Station as a Local Train (Railway) station. Since the 1980s, this train line has stopped operating and will be active again in 2016 for containers and in 2021 as a passenger train line. The shift in the function of this station has an impact on the local environment, especially the settlements around the station. On the other hand, the condition of the village was not ready for empowerment to welcome the bustling station activities. Among them, business facilities for parking and small trade that have not been well organized, and there is no passenger waiting area. This study aims to determine the basic, supporting and settlement aspects of settlements adjoining the station socially and economically in a sustainable aspect. So that there are proposals for settlement concept designs that support station activities through the role of active cooperation between the community and parties involved in the development of sustainable cities. Literature studies and field observations are used to find solutions to this problem. In addition, field observations in case studies were carried out through a SWOT analysis. The result is a sustainable settlement concept with community participation, which is integrated through station support facilities managed by the surrounding community such as stalls, minibus stops for waiting, and parking lots through sustainable optimization of commercial land productivity